Regulation of injury-induced skeletal myofiber regeneration by glucose transporter 4 (GLUT4) - Tyler J. Sermersheim; LeAnna J. Phillips; Parker L. Evans; Barbara B. Kahn; Steven S. Welc; Carol A. Witczak (Skeletal Muscle, 2024)
Abstract Background Insulin resistance and type 2 diabetes impair cellular regeneration in multiple tissues including skeletal muscle. The molecular basis for this impairment is largely unknown. Glucose uptake via glucose transporter GLUT4 is impaired in insulin resistance. In healthy muscle, acute injury stimulates glucose uptake. Whether decreased glucose uptake via GLUT4 impairs muscle regeneration is presently unknown. The goal of this study was to determine whether GLUT4 regulates muscle glucose uptake and/or regeneration following acute injury. Methods Tibialis anterior and extensor digitorum longus muscles from wild-type, control, or muscle-specific GLUT4 knockout (mG4KO) mice were injected with the myotoxin barium chloride to induce muscle injury. After 3, 5, 7, 10, 14, or 21 days (in wild-type mice), or after 7 or 14 days (in control & mG4KO) mice, muscles were isolated to examine [3H]-2-deoxyglucose uptake, GLUT4 levels, extracellular fluid space, fibrosis, myofiber cross-sectional area, and myofiber centralized nuclei. Results In wild-type mice, muscle glucose uptake was increased 3, 5, 7, and 10 days post-injury. There was a rapid decrease in GLUT4 protein levels that were restored to baseline at 5–7 days post-injury, followed by a super-compensation at 10–21 days. In mG4KO mice, there were no differences in muscle glucose uptake, extracellular fluid space, muscle fibrosis, myofiber cross-sectional areas, or percentage of centrally nucleated myofibers at 7 days post-injury. In contrast, at 14 days injured muscles from mG4KO mice exhibited decreased glucose uptake, muscle weight, myofiber cross sectional areas, and centrally nucleated myofibers, with no change in extracellular fluid space or fibrosis. Conclusions Collectively, these findings demonstrate that glucose uptake via GLUT4 regulates skeletal myofiber regeneration following acute injury.